Soil Salinity and Food Security in India - Kumar, Pardeep; Sharma, Pradeep K. (Frontiers in Sustainable Food Systems, 2020)
India would require around 311 Mt of food grains (cereals and pulses) during 2030 to feed around 1.43 Bn people, and the requirement expectedly would further increase to 350 MT by 2050 when India’s population would be around 1.8 Bn. To achieve food security in the country, the attempts need to focus on both area expansion under agriculture as well as rise in crop productivity. Massive urbanization is putting pressure on agricultural lands, resulting in shrinking of land holdings. The possibility of area expansion under agriculture, therefore, exists in restoring the degraded lands. Nearly 147 Mha of land is subject to soil degradation, including 94 Mha from water erosion, 23 Mha from salinity/alkalinity/acidification, 14 Mha from waterlogging/flooding, 9 Mha from wind erosion and 7 Mha from a combination of factors due to different forces. Government of India has fixed a target of restoring 26 Mha of degraded lands, including salt affected soils, by the year 2030 to ensure food security for the people. Around 6.73 Mha area in India is salt affected. Estimates suggest that every year nearly 10% additional area is getting salinized, and by 2050, around 50% of the arable land would be salt affected. Saline soils occupy 44% area covering twelve states and one Union Territory, while sodic soils occupy 47% area in eleven states. The establishment of Central Soil Salinity Research Institute in the country in 1969 was a landmark step towards restoring salt affected soils. Many State Agricultural Universities are also engaged in these researches. Several innovative technologies have been developed and on-farm tested. Gypsum-based sodic soil reclamation, sub-surface drainage of waterlogged saline lands, salt tolerant crop varieties and improved agroforestry techniques are some of the shining testimonies. Reclamation of 1.5 Mha salt affected soils during last four decades has added about 15 million tonnes of food grains to the National food basket with an additional income of Rs.13.50 billion annually, besides generating 8.5 million man-days each year as on-farm and off-farm employment. The ongoing consistent research efforts for the management and reclamation of such soils would hopefully continue ensuring food security in the country.